Past, Present and Future of the Innovation Process - Žižlavský, Ondřej (InTech, 2013)
In the modern globalized world, innovation is a basic prerequisite for economic development and the preservation of competitiveness. However, there is still no generally accepted definition of innovation or the innovation process; individual authors use their own definitions, often formed from different concepts. This paper compares these definitions using methods of analysis and synthesis, constructing its own conceptual framework of the innovation process reflecting the key characteristics that are identical or similar in many of the compared definitions. When constructing a new definition and model, it is necessary to bear in mind that innovation is not an isolated activity but rather an entire process or even sequence of processes. With true innovation, every partial process must be successfully completed. This process as a whole becomes the starting point for further research, measurement and the management control of innovation performance under the postdoc research project Innovation Process Performance Assessment: a Management Control System Approach in the Czech Small and Medium-sized Enterprises No. 13-20123P of the Czech Science Foundation.

In the modern globalized world, innovation is a basic prerequisite for economic development and the preservation of competitiveness. However, there is still no generally accepted definition of innovation or the innovation process; individual authors use their own definitions, often formed from different concepts. This paper compares these definitions using methods of analysis and synthesis, constructing its own conceptual framework of the innovation process reflecting the key characteristics that are identical or similar in many of the compared definitions. When constructing a new definition and model, it is necessary to bear in mind that innovation is not an isolated activity but rather an entire process or even sequence of processes. With true innovation, every partial process must be successfully completed. This process as a whole becomes the starting point for further research, measurement and the management control of innovation performance under the postdoc research project Innovation Process Performance Assessment: a Management Control System Approach in the Czech Small and Medium-sized Enterprises No. 13-20123P of the Czech Science Foundation.
Past, Present and Future of the Innovation Process
Keywords: Innovation; innovation process; conceptual framework; model; development; Innovation; innovation process; conceptual framework; model; development